2022
DOI: 10.11591/edulearn.v16i1.17787
|View full text |Cite
|
Sign up to set email alerts
|

The role of speech style between teacher and student in learning English

Abstract: This study examined the role of speech style between teachers and students in learning English. This study was ex post facto research, using quantitative approach. The students at English Department of Madura University, Indonesia were the population in this research. A sample was decided using proportional stratified random sampling technique. The data were analyzed by simple regression technique. The result of the study showed that the role of speech style between the teachers and the students in learning En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Andzik et al [52] point out that there is a statistically significant association between the professional traits of the teacher linked to the amount of training he acquired with his ability to communicate with his students, that is, teachers with greater mastery will have to develop various didactic support strategies for their students around their communication. In the same line of results, Amiruddin and Jannah [53] concluded that teachers who use an appropriate communication style will build conditions for class sessions to provide significant contributions to the students' acquisition of knowledge. As evidenced in all the investigations to which reference is made, they indicate that there is a relationship between the attitudes or professional traits linked to the domain of the subject, their innovative capacity or the style of their communication, with respect to the activities or strategies in the sessions of class and that contribute to the improvement of student learning.…”
Section: Results Of Inferential Analysis and Discussionmentioning
confidence: 87%
“…Andzik et al [52] point out that there is a statistically significant association between the professional traits of the teacher linked to the amount of training he acquired with his ability to communicate with his students, that is, teachers with greater mastery will have to develop various didactic support strategies for their students around their communication. In the same line of results, Amiruddin and Jannah [53] concluded that teachers who use an appropriate communication style will build conditions for class sessions to provide significant contributions to the students' acquisition of knowledge. As evidenced in all the investigations to which reference is made, they indicate that there is a relationship between the attitudes or professional traits linked to the domain of the subject, their innovative capacity or the style of their communication, with respect to the activities or strategies in the sessions of class and that contribute to the improvement of student learning.…”
Section: Results Of Inferential Analysis and Discussionmentioning
confidence: 87%
“…It is in line with the statement of (Nawas, 2020) and (Male, 2018) asserting that when language learners speak a second language without stress or worry, they convey their thoughts and ideas in an ordered, clear, and acceptable manner. Language learners, on the other hand, articulate their thoughts and deliver messages with a sense of perplexity that is difficult for listeners to comprehend if they lack selfconfidence, or are in a condition of high anxiety (Amiruddin & Jannah, 2022b). This will also have an impact on language learners' fluency while communicating with a second language.…”
Section: Resultsmentioning
confidence: 99%
“…Providing students with efficient and effective environment for their input to have good performances in English language is not easy. Language environment encompasses everything the language learner hears and sees in the new language (Amiruddin & Jannah, 2022b). Teachers should have a good preparation and design the classroom based on their objectives in learning.…”
Section: Introductionmentioning
confidence: 99%